Strategi Penetapan Harga Dalam Meningkatkan Pendapatan Usaha Warung Kopi Rakyat BP7 - Rumiris Siahaan; Sarwoto Sarwoto; Rakhmawati Purba; Mei Ferdin Zai; Jesica Mia Elisabeth Silalahi; Mhd Rizky Dwi Anggoro; Mhd Rizky Pradana; Mhd Ardana Pratama; Raja Mangaratua Nainggolan (STIE Bina Karya, 2026)
One of the micro, small, and medium enterprises (MSMEs) is Warung Kopi Rakyat BP7, which operates in the culinary sector. It not only serves as a place to sell drinks and snacks, but also serves as a space for social interaction, gathering, discussion, and networking among residents. Amidst today's increasingly fierce business competition, pricing strategy is a crucial factor influencing business success. Running a business requires an appropriate pricing strategy to attract customers, maintain customer loyalty, and increase revenue. Pricing needs to consider various aspects such as production costs, consumer purchasing power, competitor prices, product quality, and perceived customer value. It can be concluded that pricing strategy is closely related to increasing business revenue. The right price will create a balance between business profits and customer satisfaction, thus ensuring the survival and sustainability of an MSME